Alpha-Amylase Immobilization on Epoxy Containing Thiol-Ene Photocurable Materials - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR; DANIŞ, ÖZKAN; DEMİR, SERAP (KOREAN SOC MICROBIOLOGY & BIOTECHNOLOGY, 2013)
Thiol-ene polymerization is a versatile tool for several applications. Here we report the preparation of epoxide groups containing thiol-ene photocurable polymeric support and the covalent immobilization of alpha-amylase onto these polymeric materials. The morphology of the polymeric support was characterized by scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS) coupled with SEM was used to explore the chemical composition. The polymeric support and the immobilization of the enzyme were characterized by FTIR analysis. SEM-EDS and FTIR results showed that the enzyme was successfully covalently attached to the polymeric support. The immobilization efficiency and enzyme activity of alpha-amylase were examined at various pH (5.0-8.0) and temperature (30-80 degrees C) values. The storage stability and reusability of immobilized alpha-amylase were investigated. The immobilization yield was 276 +/- 1.6 mg per gram of polymeric support. Enzyme assays demonstrated that the immobilized enzyme exhibited better thermostability than the free one. The storage stability and reusability were improved by the immobilization on this enzyme support. Free enzyme lost its activity completely within 15 days. On the other hand, the immobilized enzyme retained 86.7% of its activity after 30 days. These results confirm that alpha-amylase was successfully immobilized and gained a more stable character compared with the free one.
Keywords: Thiol-ene polymerization; enzyme immobilization; alpha-amylase; UV curing; epoxide functionality; STARCH-CONVERTING ENZYMES; COVALENT IMMOBILIZATION; METHACRYLATE) MICROSPHERES; CA2+ IONS; SURFACE; PHOTOPOLYMERIZATION; PERFORMANCE; STABILITY; MEMBRANE; KINETICS